Different expression systems for production of HCV structural proteins - Mirnurollahi, Masoumeh; Irani, Shiva; Bolhassani, Azam (Archives of Advances in Biosciences, 2015)
Hepatitis C virus (HCV) is an important agent causing chronic liver infection, which often leads to liver cirrhosis and lethal hepatocellular carcinoma (HCC). At present, there is no effective HCV vaccine for prevention of hepatic disease and the standard treatment is neither economical nor fully effective in all the patients. However, vaccination based on structural and nonstructural proteins of HCV has attracted a special interest. Different heterologous systems have been used to generate the recombinant HCV core, E1, and E2 proteins including Escherichia coli, yeast, insects and mammalian cells. Further studies showed that the amounts of HCV recombinant proteins in E. coli are more suitable and un-expensive compared to other systems. It should be considered that this system is not efficient for generation of the glycosylated proteins. Thus, the structure of proteins is an important agent of selection for expression systems. The selection of expression systems will be critical for the use of recombinant proteins as an immunogen. In this mini-review, we briefly describe different expression systems for generation of the HCV recombinant structural proteins applied in vaccine design.